Development of an Efficient Gene Editing Tool in Schizochytrium sp. and Improving Its Lipid and Terpenoid Biosynthesis - Huang, Peng-Wei; Xu, Ying-Shuang; Sun, Xiao-Man; Shi, Tian-Qiong; Gu, Yang; Ye, Chao; Huang, He (Frontiers in Nutrition, 2021)
Schizochytrium sp. HX-308 is a marine microalga with fast growth and high lipid content, which has potential as microbial cell factories for lipid compound biosynthesis. It is significant to develop efficient genetic editing tool and discover molecular target in Schizochytrium sp. HX-308 for lipid compound biosynthesis. In this study, we developed an efficient gene editing tool in HX-308 which was mediated by Agrobacterium tumefaciens AGL-1. Results showed that the random integration efficiency reached 100%, and the homologous recombination efficiency reached about 30%. Furthermore, the metabolic pathway of lipid and terpenoid biosynthesis were engineered. Firstly, the acetyl-CoA c-acetyltransferase was overexpressed in HX-308 with a strong constitutive promoter. With the overexpression of acetyl-CoA c-acetyltransferase, more acetyl-CoA was used to synthesize terpenoids, and the production of squalene, β-carotene and astaxanthin was increased 5.4, 1.8 and 2.4 times respectively. Interestingly, the production of saturated fatty acids and polyunsaturated fatty acids also changed. Moreover, three Acyl-CoA oxidase genes which catalyze the first step of β-oxidation were knocked out using homologous recombination. Results showed that the production of lipids increased in the three knock-out strains. Our results demonstrated that the A. tumefaciens-mediated transformation method will be of great use for the study of function genes, as well as developing Schizochytrium sp. as a strong cell factory for producing high value products.